Gateway load balancing and routing selection scheme of MANET in disaster scenario - Nor Aida, M.; Sarkar, N.I.; Cusack, B. (2016)
After disaster occurs like earthquake, it is common results of collapse structure. It is impossible for disaster victims make use of communication devices such as cellular phones, iPad or laptop to communicate with their family and friends who are trapped in the disaster when the devices become unworkable due to service communication failure in that disaster area. With infrastructure less and decentralize features, mobile ad hoc network (MANET) is ideal to be one of the options to solve this problem. Therefore, the important functionalities of MANET that allows users to create dynamically configurable wireless networks without fixed infrastructure, using common devices like mobile phones was very helpful. Nodes (victims or rescue team devices) can be a source, destination or relay of the information. The objective of this research is to develop a better gateway load balancing and routing selection scheme to improve performance of MANET in disaster scenario. This scheme designed to make the task even between gateways and to simplify the route selection. Results obtained have shown that the proposed schemes can reduce network congestion and consequently can achieve better network performances. Performances will be measured with several metrics such as fairness, throughput and packet delay.